1995
DOI: 10.1002/jlb.58.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Role of interferon-γ in immune cell regulation

Abstract: In 1965 Wheelock reported that phytohemagglutinin could induce from human leukocytes an interferon-like virus inhibitor [1]. This substance, which turned out to be interferon-gamma (IFN-gamma), has been the subject, directly or indirectly, of thousands of scientific publications since that initial report. Past research has led to the general conclusion that IFN-gamma is much more than an interferon in that it has broader effects on the various arms of the immune system than most any other lymphokine or cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
208
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(220 citation statements)
references
References 11 publications
7
208
0
4
Order By: Relevance
“…IFN-c has a great impact on the regulation of the immune response [60] since many immune cells express the IFN-c receptor and respond to IFN-c: IFN-c stimulates the differentiation of Th1 cells, inhibits the differentiation of Th2 cells [61] and activates cytotoxic T cells and NK cells [62]. Furthermore IFN-c influences antibody production by promoting the secretion of IgG2a by B cells [63] and stimulates macrophages to produce tumor necrosis factor (TNF), IL-1, IL-6 and IL-8 [64].…”
Section: Ifn-cmentioning
confidence: 99%
“…IFN-c has a great impact on the regulation of the immune response [60] since many immune cells express the IFN-c receptor and respond to IFN-c: IFN-c stimulates the differentiation of Th1 cells, inhibits the differentiation of Th2 cells [61] and activates cytotoxic T cells and NK cells [62]. Furthermore IFN-c influences antibody production by promoting the secretion of IgG2a by B cells [63] and stimulates macrophages to produce tumor necrosis factor (TNF), IL-1, IL-6 and IL-8 [64].…”
Section: Ifn-cmentioning
confidence: 99%
“…Accumulation of IFN can thus be assumed to contribute to suppression of tumor progression, this cytokine being both directly cytotoxic to H5V cells 39 and capable of stimulating the granzyme /perforinmediated cytotoxic activity of effector immune cells. 40 Suppression of distant metastases is associated with reduction of PAI -1 expression in livers. Hemangioma progression is known to involve the recruitment of host endothelial cells into lesions, which has been reported to depend on the release of proangiogenic and proteolytic factors by transformed and stromal cells.…”
Section: Potential Mechanism Of Mvmp and Mvmp / Ip -10 Action Againstmentioning
confidence: 99%
“…We chose to study interferon gamma (IFN-g) gene transfer owing to its ability to upregulate expression of major histocompatibility complex (MHC) I, enhance natural killer (NK) cell and T cell activity, inhibit tumor cell growth directly and inhibit angiogenesis. [15][16][17][18] This study revealed that SB-mediated gene transfer into GL261 murine glioma resulted in enhanced IFN-g expression that was associated with a significant increase in survival compared with administering IFN-g-encoding DNA without SB. The survival benefit was increased further when SB-mediated IFN-g gene transfer was co-administered with CpG oligodeoxynucleotides (ODN) that activate toll-like receptor nine and potentiate inflammation.…”
Section: For Review)mentioning
confidence: 80%
“…This results is consistent with previous studies that examined the effects of IFN-g on many tumor cell lines including GL261. 16,17 SB mediates sustained IFN-g expression in vivo that correlates with prolonged survival of murine glioblastoma The effects of SB-mediated mIFN-g intratumoral gene transfer relative to mIFN-g-encoding episomal plasmid were then investigated. Three days after tumor implantation, mice were treated by intratumoral infusion of 2.5 mg of pKT2/CLP-mIFN-g with or without 0.125 mg pPGK-SB13 complexed in PEI, or treated with saline (5 ml volume delivery over 20 min; N ¼ 6/group).…”
Section: Gl261-luc Allows Real-time Tumor Quantification In Vivomentioning
confidence: 99%